2020
DOI: 10.1080/23802359.2020.1742210
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA discriminates distinct population of two deadly snakes (Reptilia: Elapidae) in Northeast India

Abstract: The DNA data of Indian snakes are scanty in the global database, especially from the northeastern states. The present study generated the mitochondrial Cytochrome b gene information of two morphologically identified deadly elapid species from Mizoram. Both, the King Cobra (Ophiophagus hannah) and Banded Krait (Bungarus fasciatus) showed monophyletic clades in the BA topology and cohesively clustered with the database sequences generated from distant geographical locations. The studied O. hannah depicted 2.7-7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Further, this molecular tool is also successfully evident in forensic science by naming the unknown snakes from their venoms (Sharma et al 2016;Smith et al 2018). The earlier study suggested significant genetic divergence was observed in the different population of two deadly snakes in India and other adjacent countries (Ophiophagus hannah and Bungarus fasciatus) (Kundu et al 2020). However, the population genetic diversity of N. naja and N. kaouthia is yet to be explored especially from Indo-Bangladesh region.…”
Section: Introductionmentioning
confidence: 99%
“…Further, this molecular tool is also successfully evident in forensic science by naming the unknown snakes from their venoms (Sharma et al 2016;Smith et al 2018). The earlier study suggested significant genetic divergence was observed in the different population of two deadly snakes in India and other adjacent countries (Ophiophagus hannah and Bungarus fasciatus) (Kundu et al 2020). However, the population genetic diversity of N. naja and N. kaouthia is yet to be explored especially from Indo-Bangladesh region.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no studies specifically on the molecular systematics of this species, several previous studies have highlighted intra-specific or geographical variability based on genetic barcoding 46 48 . Accurate species delimitation is crucial in view of the variability in snake venom composition 49 and its potential effects on antivenom efficacy 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no studies specifically on the molecular systematics of this species, several previous studies have highlighted intra-specific or geographical variability based on genetic barcoding [46][47][48]. Accurate species delimitation is crucial in view of the variability in snake venom composition [49] and its potential effects on antivenom efficacy [50].…”
Section: Introductionmentioning
confidence: 99%